2009
DOI: 10.1007/s10384-009-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage of a donor cornea depending on the donor insertion method during Descemet-stripping automated endothelial keratoplasty in porcine eyes

Abstract: The amount of endothelial damage did not differ significantly among the three different methods of donor insertion during DSAEK in this animal model, but each method exhibited a different endothelial damage pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The pig experimental model has also been used in eye banking, tissue engineering, 8 and pharmacology studies 9,10 . Several corneal surgeries have been developed using the ex vivo pig model, including radial keratotomy, thermokeratoplasty, photorefractive keratectomy, LASIK, 11 Intacs, keratophakia, keratoprosthesis, anterior lamellar keratoplasty, endothelial keratoplasties, femtosecond assisted keratoplasty, and penetrating keratoplasty 12,13 . The pig eye also remains the preferred model for the surgical training of ophthalmology residents 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The pig experimental model has also been used in eye banking, tissue engineering, 8 and pharmacology studies 9,10 . Several corneal surgeries have been developed using the ex vivo pig model, including radial keratotomy, thermokeratoplasty, photorefractive keratectomy, LASIK, 11 Intacs, keratophakia, keratoprosthesis, anterior lamellar keratoplasty, endothelial keratoplasties, femtosecond assisted keratoplasty, and penetrating keratoplasty 12,13 . The pig eye also remains the preferred model for the surgical training of ophthalmology residents 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study on porcine eyes showed no significant quantitative difference in ECL between taco, drag using forceps, or drag with suture, but each had a different specific pattern of endothelial damage. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Terry, Hoar, Wall and Ousley (2006) used SEM to compare two different corneal endothelial transplantation techniques. Still within the scope of the transplant, Hwang and Kim (2009) again opted for the use of SEM to analyse the damage caused to the corneal endothelium cells in DSAEK surgery. Villarrubia et al (2017) also chose SEM with a 100-fold magnification to analyse the stromal receptor bed from three different methods to obtain the donor button.…”
Section: Discussionmentioning
confidence: 99%